2021
DOI: 10.1155/2021/6623379
|View full text |Cite
|
Sign up to set email alerts
|

Finger Citron Extract Ameliorates Glycolipid Metabolism and Inflammation by Regulating GLP-1 Secretion via TGR5 Receptors in Obese Rats

Abstract: Finger citron (FC) is one of many traditional Chinese herbs that have been used to treat obesity. The aim of this study was to elucidate the pharmacological effects and mechanisms of FC on obese rats. Rats were fed with a high-fat diet as a model of obesity and treated with FC at three different dosages for 6 weeks. Pathology in liver tissue was observed. Glucose levels, lipids levels, and inflammatory indicators in serum were evaluated by enzyme‐linked immunosorbent assay. Furthermore, the expression of G pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…An experiment showed that TGR5 is expressed on intestinal L cells, and TGR5 receptor agonists can effectively promote the induction of GLP-1 release 149 . The increase in GLP-1 secretion can effectively regulate glucose levels, lipometabolism and inflammation 150 and plays an essential role in maintaining glucose homeostasis and improving insulin resistance 151 , 152 .…”
Section: Mechanism Of Action Of Tgr5 In Obesitymentioning
confidence: 99%
“…An experiment showed that TGR5 is expressed on intestinal L cells, and TGR5 receptor agonists can effectively promote the induction of GLP-1 release 149 . The increase in GLP-1 secretion can effectively regulate glucose levels, lipometabolism and inflammation 150 and plays an essential role in maintaining glucose homeostasis and improving insulin resistance 151 , 152 .…”
Section: Mechanism Of Action Of Tgr5 In Obesitymentioning
confidence: 99%
“…Their skin is bright yellow, wrinkled and shiny. It is also an excellent herbal medicine and has been reported to be beneficial for the liver, stomach and pancreas, as well as reduce the occurrence of hypertension and respiratory infections (Gao et al, 2020; Kim et al, 2013; Luo et al, 2020; Yang et al, 2021; Zhang, 2015). Finger citron is mainly grown in Zhejiang, Guangzhou, Sichuan and Yunan province of China.…”
Section: Introductionmentioning
confidence: 99%